Sistem Pakar Berbasis Web untuk Diagnosis Penyakit Paru Anak dengan Forward Chaining - Mochammad Raflie Lazuardi; Ika Ratna Indra Astutik; Ade Eviyanti (SMATIKA JURNAL : STIKI Informatika Jurnal, 2025)
This research aims to design an expert system using the forward chaining method to facilitate the early diagnosis of lung diseases in children, such as tuberculosis, pneumonia, and bronchitis. The system is designed to help the community, especially in areas with limited access to healthcare services, in recognizing symptoms independently. The methodology uses the stages of the Expert System Development Life Cycle (ESDLC), including problem identification, knowledge acquisition from experts, design, and testing using black box techniques. This system is capable of detecting symptoms, matching them with a rule base, and providing an initial diagnosis along with recommended actions. The implementation results show that the system can support quick and accurate medical decision-making, as well as enhance public health awareness through internet-based access.